2006
DOI: 10.1007/s10995-006-0091-1
|View full text |Cite
|
Sign up to set email alerts
|

Preconception Care in International Settings

Abstract: Objectives: This literature review briefly describes international programs, policies, and activities related to preconception care and resulting pregnancy outcomes. Methods: Electronic databases were searched and findings supplemented with secondary references cited in the original articles as well as textbook chapters, declarations, reports, and recommendations. Results: Forty-two articles, book chapters, declarations, and other published materials were reviewed. Policies, programs, and recommendations relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 22 publications
2
34
1
1
Order By: Relevance
“…[4] PCC can be delivered in many ways: the ideal approach depends on the local health system. [5] In the Netherlands, delivery of PCC in the form of an individual PCC consultation is advocated. [6] Individual consultations provide the opportunity for professional-led broad risk assessment to ensure that risk factors are not overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…[4] PCC can be delivered in many ways: the ideal approach depends on the local health system. [5] In the Netherlands, delivery of PCC in the form of an individual PCC consultation is advocated. [6] Individual consultations provide the opportunity for professional-led broad risk assessment to ensure that risk factors are not overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…The 14 policy documents in this study covered a variety of preconception health-and care-related issues that also are seen in the international setting (1)(2)(3). This study also showed that a more intense preconception care policy effort was initiated in China in the last few years at both the national and provincial level.…”
Section: Discussionmentioning
confidence: 74%
“…tem and economic level (3,10) preconception care policy research in developing countries is lacking. What is also known is that many developing countries, as they shape preconception health and care policies, adopt practice recommendations from developed countries (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Os benefícios do cuidado pré-concepcional -como, por exemplo, a redução da mortalidade materna e infantil -são reconhecidos globalmente e ratificados em conferências internacionais, as quais têm formulado recomendações e diretrizes visando à redução dos resultados adversos no processo da gravidez (Boulet, Parker, Atrash, 2006 (Brasil, 1996), que prevê não só o cuidado em contracepção, mas também voltado à concepção. A lei determina, em seu art.…”
Section: Aconselhamento Genéticounclassified